Policy and regulatory changes for a successful startup revolution - Singh, Vijay Kumar (Asian Development Bank Institute, 2020)
In January 2016, the Government of India launched the Startup India initiative, which has transformed the way in which the markets, potential entrepreneurs, and investors view startups. This transformation included a slew of policy measures intended to promote a startup culture and allow younger population members to take risk with their ideas and become
10419/238503
Keywords: Graue Literatur; startup; legal compliance; financing; investors; global partnerships; entrepreneurship; incubation